Marketing Strategy of Abian Tubuh Tofu - Ilhamudin, M. (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
The purpose of this study is to analyze the marketing strategy of Abian Tubuh tofu products in Mataram City. The type of research used is qualitative with a descriptive approach. Data analysis was carried out through three stages, namely the first stage as the data input stage on the IFE and EFE matrices, the second stage as the matching stage using the SWOT matrix, and the third stage was the formulation of a marketing strategy for Mataram City tofu products. The results of the study show that this industry actually has a strong foundation to develop in the future. The capacity and competence of the industry have been built over a long period of time as a legacy from the previous generation. can be a source of competitive advantage for the industry in the future. The highly dynamic environment has reduced sales, production activities and the supply of raw materials can be disrupted. The formulation of marketing strategies is made so that the industry can get out of an unfavorable situation, namely the industry must build core competencies, use social media in marketing, use market place, continue to build positive perceptions and attitudes about product quality, increase the creativity of craftsmen, and provide training to entrepreneurs and traders about online marketing.